Student laboratory manual for bates' nursing guide to physical examination and history taking - Hogan-Quigley, Beth; Bickley, Lynn S.; Palm, Mary Louise (Wolters Kluwer/Lippincott Williams & Wilkins, 2012)
A student laboratory manual that is written to accompany "Bates' Nursing Guide to Physical Examination and History Taking". Each chapter corresponds to a textbook chapter and contains activities to help students retain and apply the knowledge gained from the textbook.